The absence of workers in Slovenian industrial heritage - Vodopivec, Nina (Traditiones (Ljubljana), 2025)
The article points at the importance of (re)interpreting industrial heritage through the lens of workers’ experiences. After identifying difficulties in shaping industrial heritage in the context of post-socialist and post-indus-trial transformation, it examines industrial workers’ experiences of the closure of the Mura garment factory. Industrial heritage is presented as a potential site of value creation for the labour invested, where workers could regain their self-esteem, social respect and recognition, and where their dispossession could be acknowledged.
Keywords: class; deindustrializacija; deindustrialization; industrial heritage; industrijska dediščina; production workers; proizvodno delavstvo; razred; samoupravljanje; self-management; socialism; socializem; tacit knowledge; tiho znanje